Bullish Sentiment on Price Upward Trend: A Netnographic Study of Cryptocurrency Communities - Lady Joanne Tjahyana (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
Cryptocurrency as a digital decentralized currency has attracted many investors and obtained a lot of support from communities. Previous studies have concluded that there were indeed connections between community sentiment and cryptocurrency price movement. However, most of the research was conducted using sophisticated methods that are difficult to utilize by cryptocurrency investors. This research objective was to find practical ways to identify bullish sentiment during price upward trend especially during the Covid-19 omicron variant outbreak that started in the last quarter of 2021. Netnography method was used as a qualitative approach for this research to get insight from cryptocurrency communities. LunarCrush web application as a more user-friendly tool, was being used to analyze bullish sentiment and price data. During December 2021 until January 2022, 303 price upward trend data from 264 coins had been collected and analyzed. The result of this research revealed 5 categories of bullish sentiment messages from top influencers which are community booster, official information, project updates, achievement, and trading plan. However, it can be concluded that price movements were not always related to bullish sentiment. Thus, bullish sentiment should not be used as the sole factor to identify price upward trends. Furthermore, investors should join the cryptocurrency community to understand the characteristics of bullish sentiment and not just rely on data from monitoring tools. Interestingly, there were no Covid-19 related topics on bullish sentiment collected. Hence, it did not necessarily need to publish good news related to Covid-19 handling to create bullish sentiment among the investors.